Improving the understanding of plasma kallikrein contribution to arterial thrombus formation using two plant protease inhibitors - Salu, Bruno R. (2019)
The purpose of antithrombotic therapy is the prevention of thrombus formation and/or its extension with a minimum risk of bleeding. The inhibition of a variety of proteolytic processes, particularly those of the coagulation cascade, has been reported as a property of plant protease inhibitors. The role of trypsin inhibitors (TIs) from Delonix regia (Dr) and Acacia schweinfurthii (As), members of the Kunitz family of protease inhibitors, was investigated on blood coagulation, platelet aggregation, and thrombus formation. Different from Acacia schweinfurthii trypsin inhibitor (AsTI), Delonix regia trypsin inhibitor (DrTI) is a potent inhibitor of FXIa with a K-iapp of 1.3 x 10(-9) M. In vitro, both inhibitors at 100 mu g corresponding to the concentrations of 21 mu M and 15.4 mu M of DrTI and AsTI, respectively, increased approximately 2.0 times the activated partial thromboplastin time (aPTT) in human plasma compared to the control, likely due to the inhibition of human plasma kallikrein (huPK) or activated factor XI (FXIa), in the case of DrTI. Investigating in vivo models of arterial thrombus formation and bleeding time, DrTI and AsTI, 1.3 mu M and 0.96 mu M, respectively, prolonged approximately 50% the time for total carotid artery occlusion in mice compared to the control. In contrast to heparin, the bleeding time in mice treated with the two inhibitors did not differ from that of the control group. DrTI and AsTI inhibited 49.3% and 63.8%, respectively, ex vivo murine platelet aggregation induced by adenosine diphosphate (ADP), indicating that these protein inhibitors prevent arterial thrombus formation possibly by interfering with the plasma kallikrein (PK) proteolytic action on the intrinsic coagulation pathway and its ability to enhance the platelet aggregation activity on the intravascular compartment leading to the improvement of a thrombus.